Natural enemies of Maconellicoccus hirsutus (Green) (Hemiptera: Coccomorpha: Pseudococcidae), with description of a new species of Leucopina Malloch (Diptera: Chamaemyiidae) - Montes-Rodríguez, José Mauricio; Kondo, Takumasa; Gaimari, Stephen D. (Zootaxa, 2024)
The Pink Hibiscus Mealybug (PHM), Maconellicoccus hirsutus (Green) (Hemiptera: Coccomorpha: Pseudococcidae) is a quarantine pest in Colombia, however, there is little information on its distribution within the country and its natural enemies. Samples of PHM were collected in several locations in Colombia from different host-plant species and kept in breeding chambers to extract their predators and parasitoids. Two novel natural enemies of M. hirsutus were recorded, i.e., Allotropa cf. citri Muesebeck (Hymenoptera: Platygastridae) and Leucopina nyiaybsa Gaimari & Montes, sp. n. (Diptera: Chamaemyiidae) described herein. Furthermore, information on the distribution range in Colombia of the parasitoids Anagyrus kamali Moursi and Gyranusoidea indica Shafee, Alam and Agarwal (Hymenoptera: Encyrtidae) is provided. A species of Pachyneuron (Hymenoptera: Pteromalidae) was found as a possible parasitoid or hyperparasitoid somewhere in this system. Currently, in Colombia, the PHM is not considered an agricultural pest and its damage is restricted to primary hosts such as Hibiscus spp., Malvaviscus arboreus (Malvaceae) and soursop Annona muricata (Annonaceae). Prochiloneurus dactylopii (Howard) (Hymenoptera: Encyrtidae) was found as a possible hyperparasitoid. However, the number of recovered hyperparasitoids was low compared to the primary parasitoids that emerged in breeding chambers, which may explain why these species do not seem to interfere in the biological control of PHM. Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae) and Leucopina nyiaybsa Gaimari & Montes, sp. n. are considered important predators of PHM.